PENGELOLAAN WAKAF PRODUKTIF DI PONDOK PESANTREN DARUN NAJAH PLIKEN KECAMATAN KEMBARAN KABUPATEN BANYUMAS ( Pada Program Balai Latihan Kerja, Pertanian, dan Perikanan ) - Alfiah Nur Dewi Anggraheni; Rahmini Hadi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze the management of productive waqf at the Darun Najah Pliken Islamic Boarding School, Kembaran District, Banyumas Regency, especially in the Job Training Center (JTC), agriculture and fisheries programs. Productive waqf is a form of utilizing waqf assets that are managed for productive activities to support economic sustainability and the benefit of the people.In this research, a qualitative approach was used to explore the management process, challenges and impact of productive waqf on economic empowerment in the Islamic boarding school environment. Nevertheless, the management of productive waqf has had a positive impact, especially in empowering the economy of students and the surrounding community as well as increasing the independence of Islamic boarding schools. With more structured management and collaboration with various parties, the potential of productive waqf can be developed optimally for sustainable benefits for the people.The research results show that productive waqf management at the Darun Najah Islamic Boarding School involves several important stages, namely planning, resource management, program implementation and evaluation. The JTC’S program is focused on skills training for students and the surrounding community, while the agriculture and fisheries sectors are managed to generate additional income for Islamic boarding schools. The challenges faced include limited operational funds, human resource capacity, and optimal waqf asset management.